2013
DOI: 10.4067/s0717-97072013000300010
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Thermodynamic Properties of Structurally Related Phenothiazine Drugs in Aqueous Solution

Abstract: Association characteristics of amphiphilic phenothiazine drugs Fluphenazine and Trifluperazine dihydrochloride in water have been examined and their thermodynamic parameters have been calculated using conductometry. The electrical conductivity was measured as a function of concentration at various temperatures and cmc was calculated in the temperature range of 20-50°C. Thermodynamic parameters i.e. standard free energy of micellization,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The following equations (Usman and Siddiq, 2013; Usman et al, 2010, 2013) have been used for determining thermodynamic parameters, namely, free energy change ( ∆G m ), enthalpy change ( ∆H m ), and entropy change ( ∆S m ) for micellization process; Gm=()2βitalicRTlnXcmc Hm=2.3030.25em()2β0.25emRT2[]logXitaliccmcT Gm=HmT0.25emSm where R is the universal gas constant (8.314 J mol −1 K −1 ), X cmc is the mole fraction of surfactant, and β is the degree of dissociation (β=S2S1, where S 1 and S 2 are slopes of straight lines before and after micellization, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…The following equations (Usman and Siddiq, 2013; Usman et al, 2010, 2013) have been used for determining thermodynamic parameters, namely, free energy change ( ∆G m ), enthalpy change ( ∆H m ), and entropy change ( ∆S m ) for micellization process; Gm=()2βitalicRTlnXcmc Hm=2.3030.25em()2β0.25emRT2[]logXitaliccmcT Gm=HmT0.25emSm where R is the universal gas constant (8.314 J mol −1 K −1 ), X cmc is the mole fraction of surfactant, and β is the degree of dissociation (β=S2S1, where S 1 and S 2 are slopes of straight lines before and after micellization, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…Equation-1 was applied to the pre-micellar region. 27 The value of min Γ and A min are listed in Tables 1-3 and plotted in Figure 5. The results concluded that the longer hydrophobic tail of C 19 TAB is more closely packed at the air-water interface.…”
Section: Conductancementioning
confidence: 99%